Design and Production of Surface Textile Designs for Interior Furnishing: Focus on the Philosophies of Technical, Vocational And Agricultural Education in Ghana - Ibrahim, Abdul Fatahi (2014)
A Thesis submitted to the Department of Industrial Art, Kwame Nkrumah University of Science and Technology In partial fulfilment of the requirement for the degree of Master of Fine Art (Textile Design)